SCIENCE AND TECHNOLOGICAL DEVELOPMENT MODEL to START UP BUSINESS ON STUDENT ENTREPRENEURSHIP PROGRAM - Sulastri Sulastri (Lembaga Pengabdian pada Masyarakat, 2014)
Science & Technological Development for Students Entrepreneurship Program, (IbK) is one of Ministry of national Education Directorate of Higher Education program, with the aim to build a culture of entrepreneurship and creation of job opportunities for college graduates through the development and creation of new entrepreneurs both for students and for graduation’s student of universities. Target program is to create five new entrepreneurs independent, which every year supervised as many as 20 entrepreneurs. Incubation process is done by the method of training, internships, mentoring and coaching that are expected the knowledge and skills transfer in developing entrepreneurial character. In addition, to the above method is also facilitated by marketing activities, access to legal and financing and to form community among entrepreneurial students. The result of incubation produces 3 new independent entrepreneurs among others, organic fertilizer, doll-making business and Information Technology Services, which is assessed on the basis of instruments such as clarity of vision / mission and goals; access marketing, sales growth, investment and cash flow growth as well as the legality of the business. During the process of incubation showed that the character of the behavior (behavioral skills) determine the success of entrepreneurial than technical skills (technical skills). For all of this needed incubation model approach which is more oriented on the balance between behavioral skills and technical skills and also managerial skills. Therefore, the soft skill is to the factor that determines more for entrepreneurial success than hard skills. In academia, entrepreneurial learning model requires a balance between cognitive ability, psychomotor and affective.